2002
DOI: 10.1093/annonc/mdf132
|View full text |Cite
|
Sign up to set email alerts
|

Functional monitoring of anthracycline cardiotoxicity:a prospective, blinded, long-term observational study of outcome in 120 patients

Abstract: Due to the displaced cardiotoxic manifestation, functional monitoring in close connection with anthracycline administration appears to be a poorly effective method while later monitoring is essential. Current monitoring recommendations should therefore be revised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
179
1
15

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 310 publications
(198 citation statements)
references
References 36 publications
3
179
1
15
Order By: Relevance
“…13 In a large retrospective analysis, Ryberg et al reported estimated CHF risks of 0.6% and 14.5% at cumulative doxorubicin doses of 550 mg/m 2 and 1000 mg/m 2 , respectively. 14 However, a long-term prospective trial 15 showed that patients who received high cumulative doses of epirubicin (850 -1000 mg/m 2 ) had a risk of CHF that increased over a 5-year period (11% at 1 year, 20% at 5 years). Liposomal anthracyclines seemed to have an improved cardiotoxicity profile in preclinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…13 In a large retrospective analysis, Ryberg et al reported estimated CHF risks of 0.6% and 14.5% at cumulative doxorubicin doses of 550 mg/m 2 and 1000 mg/m 2 , respectively. 14 However, a long-term prospective trial 15 showed that patients who received high cumulative doses of epirubicin (850 -1000 mg/m 2 ) had a risk of CHF that increased over a 5-year period (11% at 1 year, 20% at 5 years). Liposomal anthracyclines seemed to have an improved cardiotoxicity profile in preclinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, an association of risk of CHF with age has been proposed for patients receiving anthracycline-based chemotherapy. 81,84,99 A summary of all suspected risk factors for HD chemotherapy-associated cardiac toxicity and relative preventive strategies is listed in Table 2.…”
Section: Radiation Treatmentmentioning
confidence: 99%
“…[7] Epirubicin-induced myocardial dysfunction detected early by serial tissue Doppler echocardiography has been correlated with oxidative stress markers with an unchanged LVEF during epirubicin chemotherapy. [8] DTI associated with SRI has shown its value in early detection of epirubicin-induced cardiotoxicity, and a measurable SR peak depression has been regarded as the earliest sign of left ventricular regional systolic dysfunction in epirubicintreated patients long before a clinical manifestation of heart failure.…”
Section: Discussionmentioning
confidence: 99%